THE INFLUENCE OF SOCIAL MEDIA USE AS A LEARNING RESOURCE ON LEARNING OUTCOMES IN ECONOMICS SUBJECTS OF GRADE X STUDENTS AT STATE SENIOR HIGH SCHOOL 1 SIANTAR - Maeyzar Prasetia Ndraha; Anggun Tiur Ida Sinaga; Sotarduga Sihombing (RADJA PUBLIKA, 2025)
This research is a descriptive study aimed at determining the influence of using social media as a learning resource on the economics learning outcomes of grade X students at SMA Negeri 1 Siantar. This approach was used to describe the relationship between existing variables without any manipulation or direct intervention. The instrument used was a questionnaire consisting of 25 statement items, of which 20 were declared valid (rcount > rtable 0.333) and reliable with a Cronbach's Alpha value of 0.754. The data normality test using the chi-square test showed that the data were normally distributed. The simple linear regression analysis resulted in the equation Y = 46.975 + 0.491X, indicating a positive relationship between social media and learning outcomes. Hypothesis testing using the t-test showed that tcount (4.883) > ttable (1.663), indicating a significant influence. The coefficient of determination (R²) was 0.2209, which means that the contribution of social media use to learning outcomes was 22.09%, while the remaining 77.91% was influenced by other factors not examined in this study. Thus, the use of social media as a learning resource provides a positive and significant contribution to students' learning outcomes.